SYNTHESIS OF CHITOSAN-FILM COMPOSITE TiO2 USING SORBITOL AS PLASTICIZER - Fajriati, Imelda; Sedyadi, Endaruji; Sudarlin, Sudarlin (UNIVERSITAS SEBELAS MARET (UNS), 2017)
The synthesis of chitosan–TiO2 film composite using sorbitol as plasticizer has been conducted. This research aims to develop environmental friendly plastic material which is safe for health due to the use of biodegradable chitosan - TiO2 that can block UV rays and therefore, maintain the quality of product from damage caused by UV rays. The anatase phase TiO2 nanocrystal was synthesized in chitosan matrix at room temperature and aging process. The solution was then added and blended in sorbitol for 24 hours to obtain homogeneous solution. The composite film was formed by coating method on a plate substrate, followed by drying. The characterization of film composite by XRD, TEM and FTIR showed the forming of anatase phase TiO2 nanocrystal that dispersed in chitosan matrix and formed the hydrogen bond. Meanwhile, from the physical properties characterization it was observed that the use of sorbitol as plasticizer had improved the plasticity tensile strength and elongation of the composite film. However, the excess sorbitol reduced the elasticity, tensile strength and elongation of the plastic. The best quality of plasticity obtained from film composite added by 3 % of sorbitol.